Indirect Determination of Catecholamines in Pharmaceutical Preparations by Flame Atomic Absorption Spectrophotometry - Aslam Mirza, Muhammad; Aziz Choudhary, Muhammad; Jabbar Kandhro, Abdul; Yar Khuhawar, Muhammad; Arain, Rafee; Muhammad Jhangir, Taz (Asian Journal of Chemistry, 2011)
Flame atomic absorption spectrophotometer was used for the determination of catecholamines; dopamine, adrenaline and noradrenaline based on the precipitation of catecholamines as copper(II) complex and determination of remaining copper(II) in solution by flame atomic absorption spectrophotometer. A decrease in concentration of copper(II) at pH 7 was proportional to catecholamines concentration. Linear calibration curves for dopamine, adrenaline and noradrenaline were obtained within 0.2-2.5 μg/mL with coefficient of determination (R2) within 0.9966-0.9991. A number of pharmaceutical additives tested did not affect the determination. Dopamine, adrenaline and noradrenaline in pharmaceutical preparations with relative standard deviation within 0.13-1.6 % with relative deviation from labeled values within 0.2-4.0 %.